Graphene-Molybdenum Disulphide Chitin Nanocomposite Based Passive Q-switcher - Mohd Halim, Siti Nabilah; Sapingi, Husni Hani Jameela; Mohamad Taib, Mohamad Fariz; Ahmad, Fauzan (Photonics Letters of Poland, 2022)
A simple fabrication of graphene-MoS2 nanocomposite, as well as individual graphene and molybdenum disulphide (MoS2) film has been done through a liquid phase exfoliation method using chitin as a binder. All of the developed films are integrated as a passive Q-switcher in an Erbium doped fiber laser. The graphene-MoS2 nanocomposite based passive Q-switcher is generated by a pulsed fiber laser with the shortest width of 1.63 µs and the highest signal to noise ratio of 51.01 dB. The graphene-MoS2 nanocomposite films show a better saturable absorption response compared to an individual graphene-chitin and MoS2-chitin based passive Q-switcher. Full Text: PDF References B. Zhang et al., "Recent Progress in 2D Material-Based Saturable Absorbers for All Solid-State Pulsed Bulk Lasers", Laser Photon. Rev. 14(2), 1900240 (2020). CrossRef M. Zhang, H. Chen, J. Yin, J. Wang, P. Yan, "Recent development of saturable absorbers for ultrafast lasers [Invited]", Chinese Opt. Letters 19(8), 081405 (2021). CrossRef S.A. Hussain, "Beta rhythm events predict corticospinal motor output", Scientific Reports 9(1), 1 (2019). CrossRef B. Fu, Y. Hua, X. Xiao, H. Zhu, Z. Sun, C. Yang, "Broadband Graphene Saturable Absorber for Pulsed Fiber Lasers at 1, 1.5, and 2 μm", IEEE J. Selected Topics in Quant. Electron. 20(5), 411 (2014). CrossRef S.N.M. Halim, S.N.F. Zuikafly, M.F.M. Taib, F. Ahmad, "First Principles Study on Electronic and Optical Properties of Graphene/MoS2 for Optoelectronic Application", IEEE International Conference on Semiconductor Electronics (ICSE), 29-32, (2020), CrossRef Z. Wang, H. Mu, J. Yuan, C. Zhao, Q. Bao, H. Zhang, "Graphene-Bi2Te3 Heterostructure as Broadband Saturable Absorber for Ultra-Short Pulse Generation in Er-Doped and Yb-Doped Fiber Lasers", Quant. Electron. 23(1), 195 (2016). CrossRef E.P. Randviir, D.A. Brownson, C.E. Banks, "A decade of graphene research: production, applications and outlook", Materials Today 17(9), 426 (2014). CrossRef S.N.F. Zuikafly, N.F. Razak, R.M. Rosnan, S.W. Harun, F. Ahmad, "Graphene slurry based passive Q-switcher in erbium doped fiber laser", Bull. Electr. Engin. Informat. 8(4), 1351 (2019). CrossRef W.M.F.W. Nawawi, K.-Y. Lee, E. Kontturi, R.J. Murphy, A. Bismarck, "Chitin Nanopaper from Mushroom Extract: Natural Composite of Nanofibers and Glucan from a Single Biobased Source", ACS Sustainable Chem. Engin. 7(7), 6492 (2019). CrossRef